Novel Surrogate Markers of CNS Inflammation in CSF in the Diagnosis of Autoimmune Encephalitis - Jiang, Jocelyn X.; Fewings, Nicole; Dervish, Suat; Fois, Alessandro F.; Duma, Stephen R.; Silsby, Matthew; Bandodkar, Sushil; Ramanathan, Sudarshini; Bleasel, Andrew; John, Bryne; Brown, David A.; Lin, Ming-Wei (Frontiers in Neurology, 2020)
Background: Autoimmune encephalitis (AE) is an important cause of refractory epilepsy, rapidly progressive cognitive decline and unexplained movement disorders in adults. Whilst there is identification of an increasing number of associated autoantibodies, patients remain with a high clinical probability of autoimmune encephalitis but no associated characterised autoantibody. These patients represent a diagnostic and treatment dilemma. Objective: To evaluate routine and novel diagnostic tests of cerebrospinal fluid (CSF) in patients with a high probability of AE to attempt to identify better biomarkers of neuroinflammation. Methods: Over 18 months (2016-2018), adult patients with a high clinical probability of AE were recruited for a pilot cross-sectional explorative study. We also included viral polymerase-chain-reaction (PCR) positive CSF samples and CSF from neurology patients with ‘non-inflammatory’ (NI) diagnoses for comparison. CSF was examined with standard investigations for encephalitis and novel markers (CSF light chains, and cytokines). Results and Conclusions: 32 AE patients were recruited over 18 months. Twenty-one viral controls, 10 NI controls and five other autoimmune neurological disease controls (AOND) were also included in the analysis. Our study found that conventional markers: presence of CSF monocytosis, oligoclonal bands, anti-neuronal immunofluorescence, and magnetic resonance imaging (MRI) changes could be suggestive of AE, but these investigations were neither sensitive nor specific. Promising novel makers of autoimmune encephalitis were the CSF cytokines IL-21 and IP10 which may provide better delineation between viral infections and autoimmune encephalitis than conventional markers, potentially leading to more immediate diagnosis and management of these patients.